Preparation of polyvinyl alcohol, chitosan and polyurethane-based pH-sensitive and biodegradable hydrogels for controlled drug release applications - Kamaci, Umran Duru; Kamaci, Musa (TAYLOR & FRANCIS AS, 2020)
In this study, novel hydrogels containing poly(azomethine-urethane) (PAMU), PVA and CS were prepared for controlled drug delivery application. FT-IR was used to confirm hydrogel structures. Thermal stability and mechanical behavior of the hydrogels were also investigated by using a thermogravimetric analysis (TG-DTA) and mechanical measurements. Swelling degree of the hydrogels were carried out at pH = 3, 7, and 12. Antibacterial properties of the hydrogels were also investigated using disc diffusion method. The obtained results showed that controlled drug release, swelling performance, and mechanical properties of the hydrogels were enhanced by increasing the amount of PAMU in the hydrogel matrix.
Keywords: Antibacterial; biodegradable; chitosan; drug delivery; 5-fluoro uracil; NANOCOMPOSITE HYDROGELS; CELLULOSE NANOCRYSTALS; POLYMER; DELIVERY; Materials Science; Polymer Science